Development of Optimal Technology for Drying Herbal Medicinal Raw Materials from Autumn Wormwood (Artemisia serotina Bunge) Based on Comparative Analysis - A. Kadyrbay; Z. B. Sakipova; N. A. Krishtanova; L. N. Ibragimova; M. B. Ibrayeva; A. E. Sakipov; E. N. Bekbolatova; Ch. Ridvanov; O. V. Sermukhamedova; Y. Adilbek; T. Y. Seiduali; A. K. Anartayeva; et al. (Разработка и регистрация лекарственных средств)
Introduction. Choosing the optimal method for drying medicinal plants is an important aspect of obtaining herbal materials of pharmacopoeial quality. At the site of the pharmaceutical enterprise Fitoleum LLP (Esik, Kazakhstan), a technology for obtaining herbal materials from autumn wormwood (Artemisia serotina Bunge) was developed, within the framework of which the optimal drying method was studied using IR radiation, convective drying and shadow drying in natural conditions. In parallel with the experimental approach, a method for simulating drying conditions was implemented. The development of technology for the obtaining of herbal materials is implemented using the "Quality by Design" concept, one of the principles of which is the modeling of experiments (Design of experiments, DoE). The advantage of modeling when studying the processes is that this technique allows you to simultaneously analyze several input parameters and their impact on quality indicators, while significantly reducing the number of experiments.Aim. To choose the optimal method for drying autumn wormwood herb for further production of herbal medicine or herbal materials.Materials and methods. During the experiment, the following equipment was used: a manual harvester for collecting plants, pallets or racks with a mesh bottom, infrared substrates, a convective drying oven, racks with pallets under a canopy in natural conditions, a grass cutter, vibrating sieves. Also, the study was carried out in accordance with the principles of the "Quality by Design" concept using the Minitab Statistical Software 21 program, using a statistical tool – Design of experiments (DoE).Results and discussion. The results of studies of various drying methods have shown that the most optimal is drying with IR radiation, which allows to maintain the content of essential oils (the main group of biologically active substances) at the optimal level – about 1,7 % with a raw material moisture content of no more than 13 %. The data obtained by simulating the experiment in the Minitab program were comparable to the results of the classical experimental design. The optimal method and technological parameters for drying autumn wormwood have been established – the use of IR radiation, temperature of 35–45 °C and drying time of 14–17 hours. Comparable data on the studied technological parameters of three sequentially produced series were obtained and the validity of the technological process for drying autumn wormwood was confirmed.Conclusion. Comparative analysis of the methods of drying medicinal plants – IR radiation, convective and shadow drying in natural conditions – of autumn wormwood (Artemisia serotina Bunge) was carried out. It has been established that the maximum content of essential oils (as the main group of biologically active substances) in raw materials is observed when using drying using IR radiation at a temperature of 35–45 °C for 14– 17 hours. At the same time, the residual moisture content of the drug is no higher than 13 %, which corresponds to pharmacopoeial requirements. Conducted studies of predicting optimal drying parameters using the Minitab Statistical Software 21 program showed comparability with the experimental results. Based on the results obtained, an optimal method for drying autumn wormwood herb was proposed for use in production and obtaining pharmacopoeial quality medicinal products.